Simulation Study of Different Modes of Miscible Carbon Dioxide Flooding - Ali E. Abass; Ahmed A. Gawish; Ehab M. Elakhal (Egyptian Journal of Petroleum)
Carbon dioxide flooding has been applied worldwide as a successful enhanced oil recovery. Carbon dioxide flooding may be applied as a continuous injection or as water-alternating-gas (WAG) process. Optimization of the injection mode of carbon dioxide is important for economical field application. This paper focuses on using a fully compositional simulation model for “AEB-3C” sandstone oil reservoir of one of the Western Desert oil fields in Egypt to predict the impact of CO2 miscible flooding on the reservoir oil recovery and net present value (NPV), to define the best mode of operation that is straight CO2 injection or water alternating gas (WAG) processes and to show the difference between pure and impure CO2. Moreover, several sensitivity runs were done on the oil price to show minimum profitable value of oil price when applying such a tertiary method in the subject field.The reservoir under study has been producing under a successful water flooding project since May-2010. The recovery factor by the end of water flooding project is predicted as 32%. CO2 flooding processes have started by the end of water flooding. A significant increase in the oil recovery factor was noticed due to applying this method; it reached up to 57%. Comparisons between different modes of operations were shown which showed better results when applying WAG process than that with straight CO2 injection. Moreover; sensitivities were done on the cycle periods in WAG processes and showed increase in the recovery factor with shortening the cycle periods. In addition to a comparison between pure and impure CO2 which showed very close results. Keywords: Miscible displacement, CO2 flooding, Compositional simulator, Tertiary recovery, Water alternating gas, Net present value